IMPACT OF TIMING OF INITIATION OF INFLIXIMAB ON THE RISK OF IBD-RELATED SURGERY AND COMPLICATIONS. (22nd January 2022) - Young, Denise; Thavamani, Aravind; Perez, Jaime; Moses, Jonathan
Abstract: BACKGROUND: Crohn's disease (CD) and ulcerative colitis (UC) are chronic inflammatory diseases of the gastrointestinal system. Approximately 20% of new diagnoses are pediatric patients. Treatment for pediatric IBD has changed in recent years, focusing on decreased steroid use, and shifting to early initiation of biologics, especially in those at risk for complicated disease. Infliximab (IFX) is used for induction and maintenance. Clinical trials have shown that IFX improves clinical remission rates, and decreases hospitalizations and surgery rates. However, there is conflicting long-term data on whether infliximab has changed the natural course of IBD and decreased surgical risk. OBJECTIVE: The objective of our study was to evaluate factors associated with increased risk of surgery in pediatric CD and UC patients using a large national health claims network database. METHODS: We used TriNetX database and identified patients up to age 18 years, with a diagnosis of CD or UC (using ICD 9 and 10 codes) and treated with infliximab from January 1, 2006 to October 1, 2020. For each patient, we collected data on demographics profile, medication use, IBD related surgeries, and complications. Patients were then categorized into "early treatment" and "late treatment" groups, with early treatment being those who initiated infliximab therapy within 90 days of IBD diagnosis. The primary outcome was the need for surgery (partial or total colectomy, small intestinal resection and stricturoplasty). Secondary outcome was any IBD related complications (intraabdominal abscess, fistula formation, perianal abscess, fistuloectomy and fistulotomy). RESULTS: A total of 7, 954 IBD patients met inclusion criteria, of which 5, 756 patients had CD, and 2, 198 patients had UC. There were 2366 patients who were started on infliximab therapy within 90 days of initial diagnosis and the remaining 5, 558 patients were in the late treatment group. A total of 169 (2.1%) patients underwent a major surgery and 560 (7%) patients experienced an IBD-related complication. Multivariate regression analysis did not reveal any significant association between timing of initiation of infliximab therapy and risk of surgery for both CD (OR: 1.12; 95% CI: 0.72 to 1.69, P=0.60) and UC (OR:1.57 ;95% CI: 0.91, 2.67, P=0.09). However, among CD patients, TPN use (OR: 5.45; 95% CI: 1.15 to 18.76, P = 0.014), fistulizing CD (OR: 4.59; 95% CI: 2.73 to 7.49; P <0.0001) and malnutrition (OR: 1.62; 95% CI: 1.02 to 2.47, P = 0.03), were more likely to develop IBD-related complications. There were no significant risk factors associated with greater odds of surgery or IBD-related complications in UC patients. CONCLUSION: Late initiation of infliximab therapy was not associated with increased risk of surgery or IBD-related complication compared to early therapy. Prospective studies are needed to further evaluate these findings.